2022
DOI: 10.13107/jocr.2022.v12.i04.2758
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Intraosseous Hibernoma of an Appendicular Skeleton in an Adult – A Rare Case Report

Abstract: Introduction: Hibernoma is an uncommon benign tumor composed of multivacuolated brown adipocytes described in the literature a decade back. Intraosseous hibernomas are extremely rare with propensity to affect axial skeleton. Involvement of appendicular skeleton has been reported only twice in the literature till date. Case Report: We present a case of solitary, painless mass in the left proximal tibia mimicking neoplasm in a 35-year-old male. The plain radiographs revealed a lytic lesion with well-defined mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…However, included in this series is the first reported paediatric case in a 7‐year‐old child, while the youngest patient previously reported was 35 31 . The patients in our study showed an almost even distribution between females and males; however, the aggregate of prior investigations has shown a strong female predominance 8–31 . Cancer‐related work‐up/surveillance or pain were the most common indications for imaging, similar to prior reports.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…However, included in this series is the first reported paediatric case in a 7‐year‐old child, while the youngest patient previously reported was 35 31 . The patients in our study showed an almost even distribution between females and males; however, the aggregate of prior investigations has shown a strong female predominance 8–31 . Cancer‐related work‐up/surveillance or pain were the most common indications for imaging, similar to prior reports.…”
Section: Discussionsupporting
confidence: 84%
“…Compared to prior reports, our median age of diagnosis was slightly older than previous studies (65 versus 57 years). However, included in this series is the first reported paediatric case in a 7‐year‐old child, while the youngest patient previously reported was 35 31 . The patients in our study showed an almost even distribution between females and males; however, the aggregate of prior investigations has shown a strong female predominance 8–31 .…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations